The dynamics of soil firmness change depending on its basic cultivation - Tsentylo , L. V.; Tsiuk , O. A. (Scientific Progress & Innovations, 2019)
The aim of the article is to determine the dependence of changes in the soil firmness dynamics at applying different systems of basic cultivation. Methods of the research. The following scientific methods were the methodological basis: analysis, synthesis, field, statistical. The research results. The results of research on typical black soil of the deep Right-Bank Forest-Steppe of Ukraine as to studying the soil protection effectiveness of basic cultivation variants on soil firmness are presented in the article. It was ascertained that the contour tillage does not change the range of firmness in typical black soil. Applying shallow contour-free tillage with slitting causes the firmness increase in the lower part of the soil arable layer. Firmness differences are most of all expressed in autumn, right after the basic cultivation, and in the spring-summer period, they level and, as a rule, do not reach the critical values for growing crops. The elements of scientific novelty. It was proved that the firmness of typical deep low-humic black soil is subject to changes depending on the systems of basic soil cultivation. The application of contour cultivation does not change soil firmness indices. It was determined that the shallow untreated cultivation with simultaneous slitting increases the degree of firmness in the lower part of the arable soil layer. Practical significance. Studying the dynamics of soil firmness changes in relation to the systems of basic soil cultivation was carried out in the experimental field at the Training- Research-Innovation Center of Agro-technologies of the LLC "Agro-firm Kolos" (in 2011–2017) in Skvirsky district of Kyiv region as a permanent experiment. The size of the sown area was 340 m2, the accounting area was 195 m2. The experiment was conducted in three replications. It was established that using contour cultivation in crop rotation did not change soil firmness index. The application of shallow untreated cultivation with simultaneous slitting led to increasing the soil firmness during the vegetation of maize for grain by 27% on the average, alfalfa – 1.74% as compared with systematic contouring. However, concerning wheat, the soil firmness index at the shallow untreated cultivation with simultaneous slitting decreased by 14.3% as compared with the contour cultivation.